2017
DOI: 10.1111/pbr.12496
|View full text |Cite
|
Sign up to set email alerts
|

Improving adaptation to drought stress in white pea bean (Phaseolus vulgaris L.): Genotypic effects on grain yield, yield components and pod harvest index

Abstract: Common bean (Phaseolus vulgaris L.) is the most important food legume crop in Africa and Latin America where rainfall pattern is unpredictable. The objectives were to identify better yielding common bean lines with good canning quality under drought, and to identify traits that could be used as selection criteria for evaluating drought‐tolerant genotypes. In all, 35 advanced lines were developed through single seed descent and evaluated with a standard check under drought and irrigated conditions at two locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
8
23
0
Order By: Relevance
“…The most important of these yield components regardless of the market class was the number of pods per plant, suggesting that it can be used by plant breeders as an additional and indirect selection method for seed yield. Similar results were found by [32,36,44]. This study reflected the general assumption that yield increases with growth habit such that Type IVs (climbers) are the best yielding.…”
Section: Correlations Between Seed Yield and Yield Components Of Intesupporting
confidence: 87%
See 2 more Smart Citations
“…The most important of these yield components regardless of the market class was the number of pods per plant, suggesting that it can be used by plant breeders as an additional and indirect selection method for seed yield. Similar results were found by [32,36,44]. This study reflected the general assumption that yield increases with growth habit such that Type IVs (climbers) are the best yielding.…”
Section: Correlations Between Seed Yield and Yield Components Of Intesupporting
confidence: 87%
“…[33,34,35,36] observed that water stress during flowering, pod filling stages severely affects the harvest index and the seed yield. Seed yield losses might exceed 20% if the stress occurs during the early vegetative growth and could reach up to 50% in the early pod filling [32,37,38]. As most of test bean lines were of indeterminate growth habit, effects of water stress in low altitude Mwea site were more pronounced compared to dwarf cultivars as also reported in Malawi by [39].…”
Section: Agronomic Performance Of Inter-racial Bean Lines Across Sitementioning
confidence: 76%
See 1 more Smart Citation
“…Several research reports support the observation that erratic rainfall may lead to IPCA 1 and IPCA 2 = interaction principal component one and two, respectively; ASV = AMMI stability value; E = environment; g = genotype; SR = small red; * = check variety; M = Mesoamerican gene pool; LSD = least significant difference at 5% P-value threshold serious bean yield losses, if the stress occurs during the early vegetative growth (White and Singh, 1991;Mwale et al, 2009), as it was the case in Mwea where heavy rains flooded young seedlings. These losses could reach 50%, if water stress is recorded in early pod filling (White and Singh, 1991;Blair et al, 2012;Assefa et al, 2017;Rao et al, 2017). This made us believe that the double water stress experienced by the bean crop in low altitude Mwea site explains the poor yield performance observed, regardless of the genetic background of test lines.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 9.8 million metric tons of common beans is lost annually due to drought in Africa [8] and when severe drought occurs early in crop development stages, the yield loss can be up to 80% [9,10]. Keeping in mind that over 80% of small-holder bean producers in developing countries use unimproved bean cultivars that are notoriously low yielders [11,12], there is need to select and ISSN: 2456-7132 Available online at Journals.aijr.in…”
Section: Introductionmentioning
confidence: 99%